Cost-effectiveness of Phacoemulsification Versus Combined Phacotrabeculectomy for Treating Primary Angle Closure Glaucoma - Chan, Poemen P; Li, Emmy Y; Tsoi, Kelvin K F; Kwong, Yolanda Y; Tham, Clement C (Journal of glaucoma, 2017)
The purpose of this study is to compare the cost effectiveness of phacoemulsification and combined phacotrabeculectomy for lowering intraocular pressure (IOP) in primary angle closure glaucoma (PACG) eyes with coexisting cataract. Real-life data of 2 previous randomized control trials that involved 51 medically uncontrolled PACG eyes and 72 medically controlled PACG eyes were utilized to calculate the direct cost of treatment. They were followed-up for 2 years. Cost of preoperative assessments, surgical interventions, additional procedures for managing complications and maintenance of filtration, postoperative follow-up, and cost of medications were considered. Cost data of 3 different regions (The United States, People's Republic of China, and Hong Kong) were used for comparison. The corresponding average costs for treating 1 eye with newly diagnosed PACG by phacoemulsification alone and combined phacotrabeculectomy were US$3479 and US$2439 in the United States, US$1051 and US$861 in China, and US$6856 and US$12087 in Hong Kong. Surgical and medications costs were the 2 key contributors. Combined phacotrabeculectomy was more cost-effective for IOP reduction when calculating with the United States and China cost data, but was less cost-effective when calculating with the Hong Kong cost data. The cost-effectiveness was insensitive to the costs of follow-up visit and investigations, the cost of surgical operations, and the cost of postoperative procedures, but sensitive to the cost fluctuation of medications. Furthermore, for the medically uncontrolled PACG group, phacoemulsification alone became more cost-effective when the cost of medication was reduced by >75%. Combined phacotrabeculectomy is a more cost-effective option for lowering IOP in PACG eyes with coexisting cataract, over a 2-year follow-up period.